(untitled) (PIONIR: JURNAL PENDIDIKAN, 2023)
Increasingly modern developments, teachers are required to innovate in the field of learning media. The purpose of this study was to develop learning media in the form of animated videos through science process skills, ecosystem component materials for science learning at SD V. This research was a development using the ADDIE model with five stages of the development process, namely Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques was questionnaires, the instruments used are validation and response sheet questionnaires. Validation was carried out by material experts, media experts and teacher responses. The results of this validation were carried out by material experts by 91% with a very decent category, media experts by 98% with a very decent category to use. The results of the student response trial with an average score of 85% and the results of the teacher response trial of 96%. It can be concluded that learning with mass media through animation media using a science process skills approach is very feasible to be used in class V lessons of the Science Ecosystem Component